A switchable light-responsive azopolymer conjugating protein micropatterns with topography for mechanobiological studies - Cimmino, Chiara; Netti, Paolo A.; Ventre, Maurizio (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cell shape and mechanical properties in vitro can be directed by geometrically defined micropatterned adhesion substrates. However conventional methods are limited by the fixed micropattern design, which cannot recapitulate the dynamic changes of the natural cell microenvironment. Current methods to fabricate dynamic platforms usually rely on complex chemical strategies or require specialized apparatuses. Also, with these methods the integration of dynamic signals acting on different length scales is not straightforward, whereas in some applications might be beneficial to act on both a microscale level, i.e. cell shape, and on a nanoscale level, i.e. cell adhesions. Here, we exploited a confocal laser-based technique on a light-responsive azopolymer displaying micropatterns of adhesive islands. The laser light promotes a directed mass migration and the formation of submicrometric topographic relieves. Also, by changing the surface chemistry, the surfacing topography affects cell spreading and shape. This method enabled us to monitor in a non-invasive manner the dynamic changes in focal adhesions, cytoskeleton structures and nucleus conformation that followed the changes in the adhesive characteristic of the substrate. Focal adhesions reconfigured after the surfacing of the topography and the actin filaments reoriented to co-align with the newly formed adhesive island. Changes in cell morphology also affected nucleus shape, chromatin conformation and cell mechanics with different timescales. The reported strategy can be used to investigate mechanotransduction-related events dynamically by controlling cell adhesion at a cell shape and focal adhesion levels. The integrated technique enables achieving a submicrometric resolution in a facile and cost-effective manner.